Hepatitis E Virus (HEV) Open Reading Frame 2 Antigen Kinetics in Human-Liver Chimeric Mice and Its Impact on HEV Diagnosis. (18th April 2019) - Sayed, Ibrahim M; Verhoye, Lieven; Montpellier, Claire; Abravanel, Florence; Izopet, Jacques; Cocquerel, Laurence; Meuleman, Philip
Abstract: Background: Hepatitis E virus infection (HEV) is an emerging problem in developed countries. Diagnosis of HEV infection is based on the detection of HEV-specific antibodies, viral RNA, and/or antigen (Ag). Humanized mice were previously reported as a model for the study of HEV infection, but published data were focused on the quantification of viral RNA. However, the kinetics of HEV Ag expression during infection remains poorly understood. Methods: Plasma specimens and suspensions of fecal specimens from HEV-infected and ribavirin-treated humanized mice were analyzed using HEV antigen–specific enzyme-linked immunosorbent assay, reverse transcription–quantitative polymerase chain reaction analysis, density gradient analysis, and Western blotting. Result: Open reading frame 2 (ORF2) Ag was detected in both plasma and stool from HEV-infected mice, and levels increased over time. Contrary to HEV RNA, ORF2 Ag levels were higher in mouse plasma than in stool. Interestingly, ORF2 was detected in plasma from mice that tested negative for HEV RNA in plasma but positive for HEV RNA in stool and was detected after viral clearance in mice that were treated with ribavirin. Plasma density gradient analysis revealed the presence of the noninfectious glycosylated form of ORF2. Conclusion: ORF2 Ag can be used as a marker of active HEV infection and for assessment of the effect of antiviral therapy, especially when fecal samples are not available or molecular diagnostic tests are not accessible.